2017
DOI: 10.1186/s12939-017-0577-z
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in utilization willingness of institutional care among the single seniors: evidence from rural Shandong, China

Abstract: BackgroundInstitutional care has become an urgent issue in rural China. Rural single seniors, compared with their counterparts, have lower income and are more vulnerable. Gender is also a significant factor determining long-term institutional care. This study is designed to examine the gender difference towards utilization willingness of institutional care among rural single seniors.MethodsA total of 505 rural single seniors were included in the analysis. Binary logistic regression model was used to examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 24 publications
(29 reference statements)
3
24
0
Order By: Relevance
“…We assume that the elderly living alone typically lack physical and psychological assistance and care from their family, and are therefore more willing to live in elder care institutions. Similar results were found in a study that showed that elderly people who lived alone were more willing to live in elder care institutions, for both single males and females, when compared with those who lived with children or others 38. First, as another study concluded, older people are more likely than any other section of the population to be living in single-person households 39.…”
Section: Discussionsupporting
confidence: 79%
“…We assume that the elderly living alone typically lack physical and psychological assistance and care from their family, and are therefore more willing to live in elder care institutions. Similar results were found in a study that showed that elderly people who lived alone were more willing to live in elder care institutions, for both single males and females, when compared with those who lived with children or others 38. First, as another study concluded, older people are more likely than any other section of the population to be living in single-person households 39.…”
Section: Discussionsupporting
confidence: 79%
“…47 According to some elderly, if they live in an eldercare institution, their children might be considered unfilial and could be ridiculed. 48 …”
Section: Discussionmentioning
confidence: 99%
“…20 In this study, a three-stage cluster sampling was used to select participants, as described in detail previously. 21 A total of 3923 older people were included in the analysis. We used a face-to-face interview to collect data from November 2011 to January 2012.…”
Section: Methodsmentioning
confidence: 99%